Investigating the roles of local mucosal immunity and estradiol in the generation of protective T cell responses against secondary HSV-2 infections in the female genital tract - Roth, Kristy (My University, 2015)
Genital herpes is one of the most prevalent sexually transmitted infections in the world and recent estimates indicate that over 500 million people are infected by herpes simplex virus type 2 (HSV-2). Although women are more susceptible to HSV-2 infections than men and the female genital tract is the primary site of HSV-2 infection, little is known about the generation of protective immune responses in this distinct microenvironment and how these immune responses protect against genital HSV-2 infections in women. Previous studies in our lab using an HSV-2 mouse model have found that protection against genital HSV-2 challenge in immunized mice correlates with the induction of inducible vaginal associated lymphoid tissues (iVALTs). The appearance of these structures coincides with the clearance of the virus, which suggests that protective immune responses against HSV-2 could be generated in the genital mucosa itself, without the help of draining lymph nodes. In addition, these iVALTs primarily consist of CD4+ T cells, underlying the importance of identifying and characterizing the type and function of T cells that are present in the genital mucosa and how these T cells provide specific protection against HSV-2 challenge, which has not been examined. In addition, previous studies have shown that estradiol (E2) has a protective effect against sexually transmitted viral infections, but the mechanisms by which E2 protects against these viral sexually transmitted infections (STIs) has not been examined. Therefore, the work undertaken in this thesis determines the conditions under which the genital mucosa can generate protective immune responses against HSV-2 infection and also characterizes the T cell responses that are generated in the genital mucosa of immunized mice following HSV-2 challenge. We also determined the conditions under which E2 enhances protection against genital HSV-2 infections and examined the mechanism by which E2 regulates protective T cell responses in the genital mucosa following HSV-2 infection. We first examined whether local immunization could establish effective antiviral memory responses directly in the female genital tract (FGT), without the help of draining lymph nodes, following HSV-2 infection. We found that even in the absence of secondary lymphoid organs (SLOs), mice immunized intravaginally (IVAG) with attenuated thymidine kinase-negative (TK-) HSV-2 were completely protected against genital HSV-2 challenge, but they showed delayed viral clearance and prolonged genital pathology post-immunization compared to WT mice. Although local viral-specific antibody responses were compromised and T cell-mediated anti-HSV-2 responses were delayed in the absence of SLOs, the immune responses generated in the genital mucosa were effective in protecting against HSV-2 challenge. Next, we determined whether immunization, either locally in the genital mucosa or distally via the nasal mucosa, with a non-replicating virus vaccine could establish protection against HSV-2 challenge, in the presence or absence of SLOs, to further understand the requirements for generating local effector responses in the genital tract. To do this, we immunized WT and LTα-/- mice IVAG or intranasally (IN) with a subunit vaccine (HSV-2 gD plus CpG), a heat-inactivated virus vaccine (heat-inactivated HSV-2 plus CpG), or a live attenuated virus vaccine (TK- HSV-2). All groups of mice were then challenged IVAG with WT HSV-2. Mice immunized by either route, with non-replicating vaccine, were not protected against genital HSV-2 challenge and succumbed to infection. However, treating WT and LTα-/- mice with E2 prior to immunization resulted in enhanced protection against HSV-2 challenge. Lastly, we examined the mechanism by which E2 treatment leads to enhanced protection of immunized mice following HSV-2 infection. We found that E2 treatment increased the recruitment of mucosal effector CD4+CD103+ T cells into the vaginal tract of immunized mice, following HSV-2 challenge. In addition, E2 treatment upregulated Th17 cells in the vaginal tract of mice following HSV-2 challenge, which was accompanied by an early IFNγ+ Th1 response and a decreased TNFα+ T cell response compared to mock controls. These results suggest that the use of highly immunogenic live-attenuated virus based vaccines delivered via mucosal routes can provide protection in the genital tract against subsequent genital HSV-2 infections. However, if a less immunogenic vaccine formulation, such as a subunit or inactivated virus based vaccine, or a lower dose of the attenuated virus based vaccine is delivered, either locally or distally, additional mucosal adjuvants or hormones may be required to elicit protection in the genital tract. Furthermore, the hormonal microenvironment during immunization should be a critical consideration in the development of mucosal HSV-2 vaccines as hormones present at the time of immunization may significantly alter the induction of protective immune responses in the female genital tract.